A method for preparing a methanation catalyst for coal-to-sng

The catalyst was prepared by a stepwise co-precipitation-impregnation method, which solved the problems of uneven distribution and migration of active components at high temperatures, and achieved high stability and high activity of the catalyst, thereby improving the methanation efficiency in the coal-to-natural gas process.

CN120861059BActive Publication Date: 2025-12-05HUBEI HUIHUANG SCI & TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511370388.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-24
Publication Date
2025-12-05
Estimated Expiration
2045-09-24

AI Technical Summary

Technical Problem

Existing methanation catalysts are prone to sintering at high temperatures, resulting in uneven distribution of active components, insufficient catalytic activity and stability, and the migration of divalent metal elements on the support surface in traditional methods affects catalytic performance.

Method used

The catalyst was prepared by a stepwise coprecipitation-impregnation method. First, a stable metal oxide support was formed by loading divalent metal elements through coprecipitation. Then, active nickel ions were loaded through impregnation. Combined with oxidation and reduction calcination treatment, the active components were ensured to be uniformly dispersed and fixed.

Benefits of technology

It improves the thermal stability and catalytic activity of the catalyst, enhances its resistance to carbon deposition, and improves the selectivity of the methanation reaction and the yield of methane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120861059B_ABST
    Figure CN120861059B_ABST
Patent Text Reader

Abstract

The application provides a method for preparing a methanation catalyst for coal-to-natural gas, which comprises the following steps: S1: providing a metal precursor aqueous solution, wherein the metal precursor aqueous solution comprises an aluminum salt, a divalent metal salt and a template agent, and the molar ratio of aluminum elements to divalent metal elements in the metal precursor aqueous solution is 10:0.5-2; S2: adjusting the pH of the metal precursor aqueous solution to 8-9, and aging to obtain a precursor precipitate; S3: performing first calcination treatment on the precursor precipitate to obtain a metal oxide carrier; S4: performing impregnation treatment on the metal oxide carrier in an active ion solution to obtain a catalyst precursor, wherein the active ion solution comprises a nickel salt; and S5: performing second calcination treatment on the catalyst precursor to obtain a methanation catalyst for coal-to-natural gas. The method can obtain a methanation catalyst with good catalytic activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of catalysts, in particular to a method for preparing a methanation catalyst for coal-to-synthetic natural gas. BACKGROUND

[0002] Methanation reaction is a key technology in the fields of coal-to-synthetic natural gas, syngas purification and renewable energy hydrogen storage. Its core is an efficient and stable catalyst, usually with nickel as the active component and adding additives to improve thermal stability and catalytic activity. In the coal-to-synthetic natural gas process, the raw gas (syngas) usually contains a high concentration of CO, which is easy to cause the catalyst to be deactivated by carbon deposition. In addition, Ni particles are easy to sinter at high temperatures, reducing catalytic activity. Therefore, it is crucial to develop a methanation catalyst with good anti-carbon deposition, stability and catalytic activity.

[0003] Alumina is a common methanation catalyst carrier because it has a high specific surface area and abundant pore structure, which can effectively disperse active metals, increase the exposure rate of active sites, and thus enhance catalytic efficiency. However, long-term high-temperature reaction conditions can make the alumina carrier structure unstable, leading to a decrease in specific surface area, collapse of pore structure, deterioration of pore size distribution, and other problems, affecting the diffusion of reactants and increasing the generation of by-products, reducing the selectivity of the methanation reaction and further reducing the catalytic efficiency. In traditional methods, divalent metal oxides are often physically mixed into the catalyst to improve its high-temperature stability, but these oxides still exist as independent phases and cannot form a uniform and stable composite structure, leading to uneven distribution of active sites and affecting catalytic performance. While co-precipitation with metal salts can improve the dispersion of active components and enhance the stability of the catalyst, but the divalent metal elements will volatilize and migrate during subsequent processing, covering the effective active components and affecting the catalytic activity.

[0004] To overcome the above problems and maintain the advantages of high specific surface area and high porosity of the catalyst, the catalytic activity and stability of the catalyst are optimized. Researchers have tried to use soluble metal salts to achieve uniform dispersion of metal ions through impregnation.

[0005] For example, patent CN119951511A discloses a methanation catalyst and its preparation method. This methanation catalyst uses alumina as a support, Ni as the active component, and Mg as a promoter component. The mass percentages of each component are: Al2O3 support 40-85 wt%, Mg promoter 0.5-5 wt%, and Ni active component 14-40 wt%. The preparation method includes the following steps: dissolving nickel salt and magnesium salt separately in deionized water and stirring until homogeneous; then mixing the two solutions and stirring until homogeneous; loading the mixture onto a carbon-containing alumina support using an impregnation method; and drying and calcining the impregnated product in an oven to obtain the catalyst. The catalyst support disclosed in this patent exhibits high dispersion of the active component under low metal loading conditions, resulting in good catalyst activity.

[0006] However, the problem with the aforementioned patent is that during the high-temperature calcination process, Mg... 2+ It may migrate to the surface, forming an inactive capping layer that covers the synchronously supported active component Ni, reducing exposed active sites, weakening its hydrogenation capacity, and decreasing catalytic activity. Furthermore, Mg... 2+ with Ni 2+ During adsorption at sites on the support surface, Mg 2+ Ni tends to occupy high-energy sites 2+ Aggregation in inefficient regions may lead to uneven Ni particle size distribution after reduction, making sintering more likely and resulting in poor catalyst stability.

[0007] Therefore, there is a need to provide a methanation catalyst with good catalytic activity and stability. Summary of the Invention

[0008] This application provides a method for preparing a methanation catalyst for coal-to-natural gas, the methanation catalyst prepared by this method having good catalytic activity and stability.

[0009] In a first aspect, this application provides a method for preparing a methanation catalyst for coal-to-natural gas, comprising the following steps:

[0010] S1: Provide an aqueous solution of a metal precursor, the aqueous solution of the metal precursor comprising an aluminum salt, a divalent metal salt and a template agent, wherein the molar ratio of aluminum to divalent metal in the aqueous solution of the metal precursor is 10:0.5~2; the template agent comprises polyethylene glycol; the divalent metal salt comprises at least one of magnesium salt, barium salt and calcium salt;

[0011] S2: Adjust the pH of the aqueous solution of the metal precursor to 8-9, and allow it to stand for aging to obtain the precursor precipitate;

[0012] S3: The precursor precipitate is subjected to a first calcination treatment to remove the template agent and obtain a metal oxide support;

[0013] S4: subjecting the metal oxide carrier to an impregnation treatment in an active ion solution to load active ions to obtain a catalyst precursor; wherein the active ion solution comprises a nickel salt;

[0014] S5: subjecting the catalyst precursor to a second calcination treatment to activate and fix the active ions on the carrier to obtain a methanation catalyst for coal-to-synthetic natural gas.

[0015] According to the present application, the method introduces divalent metal elements and nickel elements as active sites by a step-by-step co-precipitation-impregnation method to obtain a methanation catalyst for coal-to-synthetic natural gas. The catalyst uses alumina as the main material. The divalent metal elements are first loaded by a co-precipitation method to form a precursor precipitate, which can improve the stability of the catalyst. The precursor precipitate is converted into a metal oxide carrier by calcination treatment, which promotes the subsequent loading of active components and also stabilizes the divalent metal elements, reducing the impact of migration to the surface on the active components. Then, the active ions are loaded by an impregnation method, and after further calcination, a catalyst with good catalytic activity and stability is obtained.

[0016] Specifically, in step S1, an aluminum salt and a divalent metal ion solution are used to obtain a precursor precipitate by a co-precipitation method. The molar ratio of aluminum elements to divalent metal elements in the metal precursor aqueous solution is 10:0.5-2. The metal oxide precursor prepared using the above molar ratio is more stable. During preparation, the catalyst has a large specific surface area and pore structure through template agent guidance. The divalent metal elements and aluminum elements after co-precipitation can achieve atomic-level dispersion, and co-calcination reduces component loss and inhibits the migration phenomenon that may occur during subsequent calcination, making the catalyst have good thermal stability and catalytic stability. Among them, the catalyst prepared by selecting polyethylene glycol as a template agent and at least one of magnesium salt, barium salt, and calcium salt as a divalent metal salt has better catalytic effect;

[0017] In step S2, the pH value of the metal precursor aqueous solution is adjusted to 8-9 and then aged and precipitated, which can improve the dispersity of divalent metal ions and the uniformity of the pores;

[0018] In step S3, the precursor precipitate is subjected to a first calcination treatment to remove the template agent and obtain a metal oxide carrier with a large specific surface area and more oxygen vacancies, which enhances the stability of the catalyst and provides more stable active component anchoring sites;

[0019] In step S4, the metal oxide carrier is placed in an active ion solution for impregnation treatment, which can more completely retain the pore structure and maintain the high specific surface area of the carrier; since the carrier obtained in step S1 has more surface defects and oxygen vacancies, the active component can be better loaded and dispersed in this step; the nickel element in the active ion solution is converted into Ni active particles loaded on the surface of the carrier after reduction, which can act as an active center for methanation and catalyze the CO hydrogenation reaction, thereby directly optimizing the catalytic activity of the catalyst.

[0020] In step S5, the catalyst precursor is subjected to a second calcination treatment to activate and fix the active ions on the carrier. In this application, the divalent metal elements and active ions are loaded in steps, because the first calcination treatment can stabilize the divalent metal elements and reduce the surface migration of the divalent metal elements, thereby avoiding the adverse effects of covering or embedding the active component. After loading the active ions, the second calcination treatment is continued to oxidize and fix the active ions under aerobic conditions, and then the Ni active particles are further reduced, which can inhibit the aggregation of the Ni active particles, improve the sintering resistance, and make the catalyst have better catalytic activity and stability.

[0021] Therefore, the catalyst prepared by the above method has high methanation catalytic activity and stability, and can be applied to the production of natural gas from coal.

[0022] In some embodiments, the template agent is polyethylene glycol (PEG) with a weight average molecular weight of 2000-4000 Da.

[0023] In some of the above embodiments, the use of polyethylene glycol with the above weight average molecular weight can make the metal oxide carrier form more uniform pores, increase the active surface area of the catalyst, and further improve the reaction activity of the catalyst.

[0024] In some embodiments, the molar concentration of aluminum in the metal precursor aqueous solution in step S1 is 0.1-1 mol / L, and the divalent metal elements include magnesium and barium, wherein the molar ratio of magnesium to barium is 1:0.1-0.5.

[0025] In some of the above embodiments, the inventors found that the catalyst has better catalytic activity when a certain molar ratio of magnesium and barium is doped in the catalyst. The reason may be that, under this molar ratio, Mg 2+ As the main framework, the ionic radius and charge distribution are close to Al 3+ , which is easy to form a more uniform and stable composite metal oxide carrier structure, which can improve the specific surface area and porosity of the carrier; Ba 2+ has a larger ionic radius, and a small amount of Ba 2+Local modification of the carrier interior induces lattice expansion, increases oxygen vacancy concentration, facilitates subsequent Ni ion dispersion, increases effective active sites, and improves catalyst activity. The moderate basicity of Mg 2+ improves the surface reaction environment, reduces the incidence of side reactions (such as coke deposition and CO polymerization), and improves the catalyst's carbon deposition resistance, thereby further improving stability. The strong basicity of Ba 2+ allows it to neutralize acidic sites and promote CO2 adsorption even at low doping levels. Barium species have high thermal stability, which can delay the collapse of the carrier's pores at high temperatures and improve the stability of the catalyst. In addition, the oxygen vacancies of Ba 2+ may feed electrons to the subsequently loaded active center Ni, inducing the formation of Niδ - , accelerating H2 activation, and optimizing the catalytic activity of the prepared catalyst. However, excessive Ba doping may cause pore blockage and active site coverage, reducing catalyst activity. Further preferably, the molar ratio of magnesium to barium is controlled to be 1:0.2-0.3, and the catalyst prepared within this range has better catalytic activity.

[0026] The catalyst prepared using a certain molar ratio of magnesium and barium in the metal precursor aqueous solution in step S1 has better performance than that prepared using a certain molar ratio of magnesium and calcium. The reason may be that Ca 2+ has a smaller ionic radius and limited lattice distortion effect, resulting in reduced oxygen vacancy generation efficiency. In addition, the basicity of calcium is weaker than that of barium, and a small amount of doping has poor neutralization ability for the carrier surface acidic sites, making it difficult to effectively inhibit carbon deposition side reactions. The poor sintering inhibition ability of calcium species at high temperatures for a long time can lead to a decrease in active area and a decrease in catalyst performance.

[0027] In some embodiments, in step S2, the pH of the metal precursor aqueous solution is adjusted to 8-9 using urea, and the precursor precipitate is obtained by aging.

[0028] In some of the above embodiments, urea is not easily left over in subsequent processing, and under the above processing conditions, the precursor precipitate is more fully and dispersed, making it easier to form a pore structure conducive to mass transfer, resulting in a catalyst with better catalytic activity and stability.

[0029] In some embodiments, in step S3, the first calcination treatment conditions include calcination treatment in an oxygen-containing atmosphere at 450-550°C.

[0030] In some of the above embodiments, under the above treatment conditions, the first calcination treatment is a calcination treatment under an oxygen-containing atmosphere at 450-550°C for 2-4h, which can better remove the template agent, optimize the pore structure, and reduce carbon residues in the pores and on the surface of the carrier; meanwhile, the precursor is precipitated to form a relatively stable metal oxide carrier, thereby improving the thermal stability of the catalyst.

[0031] In some of the above embodiments, under the above treatment conditions, the second calcination treatment comprises two-stage calcination steps, i.e., first calcination treatment under an oxygen-containing atmosphere at 350-550°C for 2-3h, in which the nickel ions are converted into the oxidation state and can be stably loaded on the surface of the carrier, and then second-stage calcination treatment under a reducing atmosphere at 300-450°C for 2-4h, in which the nickel is reduced to form Ni

[0032] In some of the above embodiments, under the above treatment conditions, the second calcination treatment comprises two-stage calcination steps, i.e., first calcination treatment under an oxygen-containing atmosphere at 350-550°C for 2-3h, in which the nickel ions are converted into the oxidation state and can be stably loaded on the surface of the carrier, and then second-stage calcination treatment under a reducing atmosphere at 300-450°C for 2-4h, in which the nickel is reduced to form Ni 0 The active particle catalytic sites enable the catalyst to have good catalytic activity and stability.

[0033] It can be understood that the cooling process of the second calcination needs to be carried out in a nitrogen atmosphere to reduce the influence of re-oxidation of the active metal on the catalyst during the cooling process.

[0034] In some of the above embodiments, the step S4 comprises immersing the metal oxide carrier in an active ion solution, and the solid-liquid ratio of the metal oxide and the active ion solution is 1g:5-20mL; the molar concentration of nickel in the active ion solution is 0.5-2mol / L.

[0035] In some of the above embodiments, the solid-liquid ratio of the metal oxide and the active ion solution is controlled to be 1g:5-20mL, which can enable the active ion solution to more fully infiltrate the pores of the carrier and the loaded active components to be more dispersed; the metal oxide carrier is immersed in the active ion solution containing nickel at the above concentration range, which can achieve a relatively high Ni 2+ supply, thereby improving the activity of the catalyst.

[0036] In some of the above embodiments, in the step S4, the active ion solution further comprises a potassium salt, and the molar ratio of nickel to potassium in the active ion solution is 1:0.1-0.5.

[0037] In some of the above embodiments, the inventors have found that the addition of the potassium salt to the active ion solution in the step S4 can affect the catalytic performance of the catalyst, and the reason may be that K +It can neutralize Lewis acid sites on the surface of the Al2O3 support, reduce CO adsorption, inhibit coking effect, and improve catalyst stability; furthermore, the potassium and nickel elements supported on the support surface also form K+ after the second calcination. + -Ni 0 Collaborative interface, on the one hand, K + K can bind with acidic sites on the support surface to form stable KO-Al bonds, and its steric hindrance effect can inhibit the migration and sintering agglomeration of Ni species. On the other hand, K can act as an electron regulator, and its electron donor properties may modulate the electronic structure of Ni active centers, promoting CO σ-adsorption and - The formation of feedback bonds accelerates the breaking and dissociation of CO, optimizes the activation capacity of H2, and gives the catalyst better stability and catalytic activity.

[0038] The catalyst prepared using the above-mentioned molar ratio of nickel and potassium in step S4 exhibits better activity, possibly because, under the specified molar ratio of nickel and potassium, K... + K can better neutralize Lewis acid sites on the support, reducing the strong adsorption of excessive CO or intermediates at acidic sites, thereby reducing side reactions and carbon deposition; simultaneously, K may also donate electrons to neighboring Ni, altering the d-band filling of Ni, thus playing an electronic regulation role; furthermore, within the stated molar concentration range, K... + It is preferable for the Ni to be anchored on the support surface in the form of KO-Al, which can stabilize the Ni active particles and retain more active sites, so that Ni can both adsorb and activate CO / H2 without being over-neutralized or passivated. More preferably, when the molar ratio of nickel to potassium is 1:0.3~0.5, the catalyst prepared has better activity.

[0039] In some embodiments, in step S4, the potassium salt comprises potassium citrate and potassium nitrate, wherein the molar ratio of potassium citrate to potassium nitrate is 2.5 to 3.5:1.

[0040] In some of the above embodiments, the inventors discovered that selecting potassium citrate and potassium nitrate as potassium sources in the active ion solution during step S4 can prepare catalysts with higher catalytic activity. This may be due to the synergistic effect of potassium citrate and potassium nitrate in the catalyst preparation process: the multidentate ligand citrate ion in potassium citrate can react with Ni... 2+ Formation of stable complexes, enabling Ni 2+ Slow deposition onto the support surface reduces migration and aggregation; furthermore, the organic complex weakens the strong Ni-Al interaction, making it easier to form small-particle Ni after reduction. 0However, the use of potassium citrate alone increases the viscosity of the solution, which can result in uneven impregnation, and citrate can form organic carbon residues during calcination, which reduces the activity of the catalyst. The oxidizing gas produced by the decomposition of nitrate during calcination can remove the organic residues produced by citrate, preventing pore blockage and reducing the active surface area. In addition, the K+ ions provided by potassium nitrate can quickly pass through the pores of the carrier in the form of free inorganic salts, improving the distribution of potassium in the carrier. Furthermore, the NO3 - can slow down the local alkaline fluctuations caused by excessive citrate, further stabilizing the Ni 2+ complex, inhibiting the formation of trace amounts of Ni(OH)2, and improving the dispersion and uniformity of the nickel component on the carrier, thereby improving the overall performance of the catalyst. Therefore, the molar ratio of potassium citrate to potassium nitrate is controlled at 2.5-3.5:1. Potassium citrate maintains the stable complexation of Ni 2+ by organic ligands, reducing the agglomeration and sintering of Ni active components, and potassium nitrate optimizes the distribution of K + ions with high diffusivity, and removes the organic residues that may be produced by citrate in the subsequent process. The synergistic effect of the two can effectively improve the dispersion of Ni, improve the pore environment of the catalyst, and thus optimize the performance of the catalyst.

[0041] It should be noted that the metal salts described in the present application, including but not limited to aluminum salts, magnesium salts, barium salts, nickel salts, and potassium salts, all refer to compounds that can ionize corresponding metal ions in appropriate solvents in a broad sense. For example, magnesium salts can include but are not limited to magnesium nitrate, magnesium acetate, and magnesium chloride. As an example, in an embodiment of the present application, Al(NO3)3·9H2O is used as an aluminum salt, Mg(NO3)2·6H2O is used as a magnesium salt, Ba(NO3)2 is used as a barium salt, K3C6H5O7·H2O and KNO3 are used as potassium salts, and Ni(NO3)2·6H2O is used as a nickel salt.

[0042] In a second aspect, the present application provides a method for preparing a methanation catalyst for coal-to-synthetic natural gas, which is prepared according to the method of any one of the embodiments of the first aspect.

[0043] According to the present application, the catalyst prepared according to the method of any one of the embodiments of the first aspect has good catalytic activity and stability for the methanation of coal-to-synthetic natural gas.

[0044] In a third aspect, the present application provides a method for preparing a methanation catalyst for coal-to-synthetic natural gas, which uses coal as a carbon source and hydrogen as a raw material under the catalysis of the catalyst according to any one of the embodiments of the second aspect to obtain methane.

[0045] According to the present application, the catalyst provided by the second aspect has good catalytic activity and stability for coal-to-synthetic natural gas, and can effectively improve the yield of product methane.

[0046] Compared with the prior art, the present application has at least the following beneficial effects:

[0047] The catalyst for preparing methane prepared by the method provided by the present application has alumina as the main material, the template agent guides the carrier to have a larger specific surface area and pore structure, and has faster mass transfer efficiency; the step-by-step co-precipitation-impregnation method is used to first form a relatively stable composite metal oxide carrier, effectively improving the stability of the catalyst, and at the same time, improving the adverse effects caused by the possible migration of metal ions to the surface to cover the active components, then loading the active component Ni on the carrier, and performing oxidation / reduction calcination treatment, so that the Ni forms a bond with the surface of the carrier, which can make the metal active component more stably dispersed, and also increase the number of effective active sites of the catalyst, further optimize the CO dissociation and adsorption process, accelerate the catalytic reaction, and make the catalyst have better catalytic activity.

[0048] The catalyst is used for coal-to-synthetic natural gas, and can effectively improve the yield of methane. BRIEF DESCRIPTION OF DRAWINGS

[0049] Figure 1 It is a physical diagram of the catalyst in Example 1 in the present application. DETAILED DESCRIPTION

[0050] In the description of the present specification, each embodiment or embodiment is described in a progressive manner, and each embodiment focuses on the difference from other embodiments.

[0051] In the description of the present specification, the description of the terms “one embodiment”, “some embodiments”, “exemplary embodiment”, “example”, “specific example”, or “some examples” means that the specific features, structures, materials or characteristics described in conjunction with the embodiments or examples are included in at least one embodiment or example of the present application. In the present specification, the exemplary description of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0052] In addition, the terms “first”, “second” are only for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Therefore, the features defined with “first”, “second” can explicitly or implicitly include at least one feature. In the description of the present application, the meaning of “multiple” is at least two, for example, two, three, etc., unless otherwise specifically limited.

[0053] In the description of the present specification, "parts" refers to "mass parts" unless otherwise specified.

[0054] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are for the purpose of explanation of the present application only and are not to be understood as a limitation of the present application. In the embodiments, the specific techniques or conditions not mentioned are performed according to the techniques or conditions described in the literature in the art or according to the product manual. The reagents or instruments not mentioned the manufacturer are all conventional products that can be obtained commercially.

[0055] Example 1

[0056] Preparation of methanation catalyst for coal-to-SNG:

[0057] S1: Al (NO3) 3·9H2O, Mg (NO3) 2·6H2O, Ba (NO3) 2·3H2O were dissolved in water to obtain a metal precursor aqueous solution, wherein the concentration of Al (NO3) 3·9H2O was 0.3 mol / L, the molar ratio of Al (NO3) 3·9H2O to divalent metal elements was 10:1, and the molar ratio of Mg (NO3) 2·6H2O to Ba (NO3) 2·3H2O was 1:0.25. A template agent PEG-3350 was further added, and the concentration of the template agent was 3 wt%, and the mixture was uniformly mixed. 3+ 3+ 2+ 2+

[0058] S2: The above aqueous solution was heated and kept at 70°C, and urea with a concentration of 0.6 mol / L was added dropwise into the above aqueous solution, the pH was adjusted to 8, and the temperature was kept at 70°C for 18h aging, and the precipitate was obtained by suction filtration, and washed with water for 3 times.

[0059] S3: The precipitate was further placed in a tube furnace, air was introduced, and the temperature was increased to 500°C at a rate of 10°C / min and kept for 4h, and then cooled to room temperature to obtain a metal oxide carrier.

[0060] S4: Ni (NO3) 2·6H2O, K3C6H5O7·H2O, KNO3 were dissolved in water to obtain an active ion aqueous solution, and the metal oxide was immersed in the active ion aqueous solution, and the solid-liquid ratio was 1g:10mL, wherein the concentration of nickel nitrate was 1 mol / L, the molar ratio of nickel element to potassium element was 1:0.3, and the molar ratio of potassium citrate to potassium nitrate was 3:1, and the catalyst precursor was obtained by stirring and impregnating for 12h and filtering.

[0061] ​​​​S5: The catalyst precursor was placed in a tube furnace, air was introduced, and heated to 500°C at a rate of 10°C / min, and then nitrogen was introduced to reduce the temperature to 400°C at a rate of 10°C / min. At this temperature, a mixture of hydrogen and nitrogen (5 / 95, V / V) was introduced into the system, and after complete replacement, it was kept for 3h. The temperature was reduced to room temperature under a nitrogen atmosphere, and the obtained blocky solid was crushed and pressed to obtain a methanation catalyst for coal-to-synthetic natural gas, as shown in the physical map of Figure 1 .

[0062] Example 2

[0063] Preparation of a methanation catalyst for coal-to-synthetic natural gas:

[0064] The preparation method was substantially the same as that of Example 1, except that the molar ratio of Al 3+ to the divalent metal element in the metal precursor aqueous solution described in S1 was different, and specifically, the molar ratio of Al 3+ to the divalent metal element was 10:2.

[0065] Example 3

[0066] Preparation of a methanation catalyst for coal-to-synthetic natural gas:

[0067] The preparation method was substantially the same as that of Example 1, except that the molar ratio of Al 3+ to the divalent metal element in the metal precursor aqueous solution described in S1 was different, and specifically, the molar ratio of Al 3+ to the divalent metal element was 10:1.5.

[0068] Example 4

[0069] Preparation of a methanation catalyst for coal-to-synthetic natural gas:

[0070] The preparation method was substantially the same as that of Example 1, except that the molar ratio of Al 3+ to the divalent metal element in the metal precursor aqueous solution described in S1 was different, and specifically, the molar ratio of Al 3+ to the divalent metal element was 10:0.5.

[0071] Example 5

[0072] Preparation of a methanation catalyst for coal-to-synthetic natural gas:

[0073] The preparation method was substantially the same as that of Example 1, except that S4 was different, and specifically, Ni(NO3)2·6H2O was dissolved in water to obtain an active ion aqueous solution, and then metal oxides were soaked in the active ion aqueous solution, wherein the concentration of nickel nitrate was 1 mol / L; stirring and impregnating for 12h, and filtering to obtain a catalyst precursor;

[0074] Example 6

[0075] Preparation of methanation catalysts for coal-to-natural gas:

[0076] It is largely the same as Example 1, except that the concentration of potassium in the active ion aqueous solution in S4 is different. Specifically, the molar ratio of nickel to potassium is 1:1.

[0077] Example 7

[0078] Preparation of methanation catalysts for coal-to-natural gas:

[0079] It is largely the same as Example 1, except that the concentration of potassium in the active ion aqueous solution in S4 is different. Specifically, the molar ratio of nickel to potassium is 1:0.1.

[0080] Example 8

[0081] Preparation of methanation catalysts for coal-to-natural gas:

[0082] It is largely the same as Example 1, except that the concentration of potassium in the active ion aqueous solution in S4 is different. Specifically, the molar ratio of nickel to potassium is 1:0.5.

[0083] Example 9

[0084] Preparation of methanation catalysts for coal-to-natural gas:

[0085] Similar to Example 1, except that the types of divalent metal elements in S1 are different. Specifically, Al(NO3)3·9H2O, Mg(NO3)2·6H2O, and Ca(NO3)2·4H2O are dissolved in water to obtain an aqueous solution of the metal precursor. 3+ The molar ratio of divalent metals is 10:1. Among the divalent metals, Mg... 2+ Ca 2+ The molar ratio is 1:0.25.

[0086] Example 10

[0087] Preparation of methanation catalysts for coal-to-natural gas:

[0088] Similar to Example 1, except that the types of divalent metal elements in S1 are different. Specifically, Al(NO3)3·9H2O and Mg(NO3)2·6H2O are dissolved in water to obtain an aqueous solution of the metal precursor. 3+ The molar ratio of divalent metals is 10:1, and the only divalent metal is Mg. 2+ .

[0089] Example 11

[0090] Preparation of methanation catalyst for coal-to-SNG:

[0091] The same as Example 1, except that the molar ratio of divalent metal elements in S1 is different, specifically, the molar ratio of Mg 2+ , Ba 2+ in the divalent metal elements is 1:0.1.

[0092] Example 12

[0093] Preparation of methanation catalyst for coal-to-SNG:

[0094] The same as Example 1, except that the molar ratio of divalent metal elements in S1 is different, specifically, the molar ratio of Mg 2+ , Ba 2+ in the divalent metal elements is 1:0.2.

[0095] Example 13

[0096] Preparation of methanation catalyst for coal-to-SNG:

[0097] The same as Example 1, except that the molar ratio of divalent metal elements in S1 is different, specifically, the molar ratio of Mg 2+ , Ba 2+ in the divalent metal elements is 1:0.3.

[0098] Example 14

[0099] Preparation of methanation catalyst for coal-to-SNG:

[0100] The same as Example 1, except that the molar ratio of divalent metal elements in S1 is different, specifically, the molar ratio of Mg 2+ , Ba 2+ in the divalent metal elements is 1:0.5.

[0101] Example 15

[0102] Preparation of methanation catalyst for coal-to-SNG:

[0103] The same as Example 1, except that the type of divalent metal elements in S1 is different, specifically, Al(NO3)3·9H2O and Ba(NO3)2·3H2O are dissolved in water to obtain a metal precursor aqueous solution, the molar ratio of Al 3+ , divalent metal elements is 10:1, and the divalent metal elements are only Ba 2+ .

[0104] Example 16

[0105] Preparation of methanation catalyst for coal-to-SNG:

[0106] The same as example 1, the only difference is that the kind of potassium salt in the active ion aqueous solution in S4 is different, specifically, Ni(NO3)2·6H2O, KCl, KNO3 are dissolved in water to obtain the active ion aqueous solution, and the molar ratio of potassium chloride and potassium nitrate is 3:1.

[0107] Example 17

[0108] Preparation of methanation catalyst for coal-to-SNG:

[0109] The same as example 1, the only difference is that the molar ratio of potassium salt in the active ion aqueous solution in S4 is different, specifically, the molar ratio of potassium citrate and potassium nitrate is 2:1.

[0110] Example 18

[0111] Preparation of methanation catalyst for coal-to-SNG:

[0112] The same as example 1, the only difference is that the molar ratio of potassium salt in the active ion aqueous solution in S4 is different, specifically, the molar ratio of potassium citrate and potassium nitrate is 4:1.

[0113] Comparative example 1

[0114] Preparation of methanation catalyst for coal-to-SNG:

[0115] S1: Al(NO3)3·9H2O is dissolved in water to obtain a metal precursor aqueous solution, wherein the concentration of Al 3+ is 0.3 mol / L, then a template agent PEG-3350 is added, the concentration of the template agent is 3wt%, and the mixture is uniformly mixed;

[0116] S2: The above aqueous solution is heated and kept at 70℃, and urea with a concentration of 0.6 mol / L is added dropwise into the above aqueous solution, the pH is adjusted to 8, the temperature is kept at 70℃, and the aging is kept for 18h, then the precursor precipitate is obtained by suction filtration, and washed with water for 3 times;

[0117] S3: The precursor precipitate is placed in a tube furnace, air is introduced, heated to 500℃ at a heating rate of 10℃ / min, kept for 4h, and then cooled to room temperature to obtain a metal oxide carrier;

[0118] S4: The metal oxide is immersed in an active ion aqueous solution again, with a solid-liquid ratio of 1 g:10 mL, wherein the concentration of potassium citrate in the active ion aqueous solution is 0.09 mol / L, the concentration of potassium nitrate is 0.03 mol / L, the concentration of nickel nitrate is 1 mol / L, the concentration of magnesium nitrate is 0.024 mol / L, and the concentration of barium nitrate is 0.006 mol / L (i.e., the molar ratio of Al 3+ , the molar ratio of the divalent metal elements Mg 2+ , Ba 2+ is 1:0.25, the molar ratio of the nickel element and the potassium element is 1:0.3, and the molar ratio of potassium citrate and potassium nitrate is 3:1), stirring and impregnating for 12 h, and filtering to obtain a catalyst precursor.

[0119] S5: The catalyst precursor is placed in a tube furnace, air is introduced, heating is performed at a rate of 10 ℃ / min to 500 ℃ and holding for 3 h, then nitrogen is introduced to reduce the temperature to 400 ℃ at a rate of 10 ℃ / min, at this temperature, a hydrogen-nitrogen mixed gas (V / V is 5 / 95) is introduced into the system, after complete replacement, holding for 3 h, and reducing the temperature to room temperature under a nitrogen atmosphere, the obtained block solid is crushed and formed to obtain a methanation catalyst for coal-to-synthetic natural gas.

[0120] Test section

[0121] Methanation reaction performance test:

[0122] 500 mg of the catalyst is ground to a particle size of 40-60 meshes, and is loaded into a stainless steel fixed bed reactor with a tube diameter of 10 mm, inert filler SiC is placed in the reactor to ensure uniform gas flow channel, and the catalyst layer is kept tight but not compressed and deformed.

[0123] High-purity nitrogen is introduced before the reaction, with a flow rate of 300 mL / min, heating to 400 ℃ and holding for 30 min, stabilizing the bed temperature, then switching the nitrogen to the feed gas for methanation reaction, and sampling after the catalyst is stably operated for 30 min under the reaction conditions. The outlet gas is analyzed by gas chromatography, and the inlet and outlet flow rates of the feed gas and the volume fractions of each component are recorded.

[0124] The methanation reaction is set as follows:

[0125] Reaction temperature: 400 ℃

[0126] Reaction pressure: 0.1 MPa

[0127] Space velocity: 5000 h -1

[0128] Feed gas (by volume fraction): CO: 10%, CO2: 3%, H2: 87%

[0129] The gas chromatography was set as follows:

[0130] Model: Agilent 7890

[0131] Detector: Thermal conductivity detector

[0132] Column: Agilent J&W Molsieve 5A packed column (30 m x 0.32 mm x 25 µm), Porapak Q packed column (2 m x 4 mm, 80-100 mesh). The two columns were switched by a program-controlled switching valve (6-port).

[0133] CO selectivity calculation:

[0134]

[0135] CO2 conversion calculation:

[0136]

[0137] CH4 selectivity calculation:

[0138]

[0139] The catalysts prepared in Examples 1-18 and Comparative Example 1 were respectively subjected to reaction evaluation according to the above evaluation method, and the detailed evaluation results of the catalysts measured when the catalysts were stably tested for 1 h under the reaction conditions are given in Table 1, and the CH4 selectivity change results of the catalysts tested for 10 h and continuously tested for 200 h are shown in Table 2.

[0140] Table 1 CO2 conversion of catalysts x Methanation reaction evaluation results (reaction bed temperature 400℃)

[0141]

[0142] Table 2 CH4 selectivity change results of catalysts with reaction time

[0143]

[0144] According to Tables 1 and 2, the catalysts obtained in each example have lower CO selectivity, higher CO2 conversion rate and CH4 selectivity than Comparative Example 1. The CO selectivity index refers to the distribution of CO in the reaction product, and low CO selectivity means that CO is efficiently converted, the amount of residual CO is small, and the side reaction of generating CO is effectively inhibited. The CO2 conversion rate index refers to the consumption rate of feed CO2 in the reaction, and high CO2 conversion rate means higher carbon raw material utilization rate. The CH4 selectivity index refers to the distribution of CH4 in the reaction product, and high CH4 selectivity means that the carbon-containing raw material is efficiently converted into CH4. Therefore, the catalysts provided by the present application have good catalytic activity for the methanation of coal-to-synthetic natural gas. The reason may be that in Comparative Example 1, when magnesium, barium, nickel and potassium elements are simultaneously loaded by the impregnation method, Mg 2+ and Ba 2+ may exist in a surface enrichment state and cannot form a stable interface structure, which greatly reduces the anchoring ability of Ni; during calcination treatment, Mg and Ba elements are prone to migration, which may form a blocking layer on the surface, causing large NiO agglomeration or directly covering the reduced Ni active sites, resulting in mass transfer resistance and reducing the activity of the catalyst; unevenly distributed Mg and Ba elements may further cause surface coating and form carbon deposition, which reduces the catalytic activity and stability of the catalyst.

[0145] According to Examples 1 to 4, the molar ratio of aluminum elements to divalent metal elements in the metal precursor aqueous solution has a certain influence on the activity of the catalyst. When the molar ratio of aluminum elements to divalent metal elements is 10:1 to 1.5, the catalyst has better activity.

[0146] According to Examples 1, 5 to 8, when loading active ions, introducing a certain concentration of potassium elements has a certain influence on the activity of the catalyst; the molar ratio of nickel elements to potassium elements also has a certain influence on the activity of the catalyst. When the molar ratio of nickel elements to potassium elements in the active ion solution is 1:0.3 to 0.5, the catalyst prepared has better activity.

[0147] According to Examples 1 and 9, the type of divalent metal elements has a certain influence on the activity of the catalyst. When magnesium and barium are selected as divalent metal elements, the catalyst has better catalytic activity.

[0148] According to Examples 1 and 10 to 15, the molar ratio of divalent metal elements has a certain influence on the activity of the catalyst. When the molar ratio of magnesium elements to barium elements in the metal precursor aqueous solution is 1:0.2 to 0.3, the catalyst has better catalytic activity and stability.

[0149] According to the embodiments 1, 16, it is known that the type of potassium salt in the active ion solution has certain influence on the activity of the catalyst, and the catalytic activity of the catalyst is better when potassium citrate and potassium nitrate are selected as the potassium salt.

[0150] According to the embodiments 1, 17 and 18, it is known that the molar ratio of potassium salt in the active ion solution has certain influence on the activity of the catalyst, and the activity of the catalyst is better when the molar ratio of potassium citrate and potassium nitrate is 2.5-3.5:1.

[0151] In addition, it can be known from the data in Table 2 that the retention rate of CH4selectivity of the catalyst obtained in the embodiment 1 during the reaction for 200 h is 99.9%, and the catalytic stability is better.

[0152] Finally, it should be noted that: the above embodiments are only used to illustrate the technical solutions of the present application, and not to limit them; although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that: it can still modify the technical solutions recorded in the foregoing embodiments, or make equivalent replacement for part or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method of preparing a methanation catalyst for coal to natural gas, characterized by, The method comprises the following steps: S1: providing a metal precursor aqueous solution, the metal precursor aqueous solution comprising an aluminum salt, a divalent metal salt and a template agent, wherein the molar concentration of aluminum elements in the metal precursor aqueous solution is 0.1-1 mol / L, the molar ratio of aluminum elements to divalent metal elements is 10:0.5-2; the template agent comprises polyethylene glycol; the divalent metal elements comprise magnesium elements and barium elements, and the molar ratio of magnesium elements to barium elements is 1:0.1-0.5; S2: adjusting the pH of the metal precursor aqueous solution to 8-9, and obtaining a precursor precipitate by standing and aging; S3: performing first calcination treatment on the precursor precipitate to remove the template agent and obtain a metal oxide carrier; S4: performing impregnation treatment on the metal oxide carrier in an active ion solution to load active ions and obtain a catalyst precursor; wherein the active ion solution comprises a nickel salt and a potassium salt, and the molar ratio of nickel elements to potassium elements in the active ion solution is 1:0.1-0.5; S5: performing second calcination treatment on the catalyst precursor to activate and fix the active ions on the carrier, and obtaining a methanation catalyst for coal-to-synthetic natural gas.

2. The method of claim 1, wherein, The step S2 comprises: adjusting the pH of the metal precursor aqueous solution to 8-9 by using urea, and obtaining a precursor precipitate by standing and aging.

3. The method of claim 1, wherein, In the step S3, the conditions of the first calcination treatment comprise calcination treatment at 450-550 DEG C for 2-4 h in an oxygen-containing atmosphere.

4. The method of claim 1, wherein, In the step S5, the conditions of the second calcination treatment comprise calcination treatment at 350-550 DEG C for 2-3 h in an oxygen-containing atmosphere, and then calcination treatment at 300-450 DEG C for 2-4 h in a reducing atmosphere, wherein the reducing atmosphere comprises hydrogen and nitrogen, and the volume fraction of hydrogen is 5%-10%.

5. The method of claim 1, wherein, The step S4 comprises: immersing the metal oxide carrier in the active ion solution, and the solid-liquid ratio of the metal oxide carrier to the active ion solution is 1 g:5-20 mL; and the molar concentration of nickel elements in the active ion solution is 0.5-2 mol / L.

6. The method of claim 1, wherein, In the step S4, the potassium salt comprises potassium citrate and potassium nitrate, and the molar ratio of potassium citrate to potassium nitrate is 2.5-3.5:

1.

7. A methanation catalyst for coal to natural gas, characterized by, The method is prepared according to any one of claims 1-6.

8. A method of coal to natural gas production, characterized by, The natural gas is prepared by using coal as a carbon source and hydrogen as a raw material and catalyzing by the methanation catalyst according to claim 7.

Citation Information

Patent Citations

  • Catalyst for preparing substitute natural gas by using coal based synthesis gas, and preparation method thereof

    CN102500387A

  • Nickel iron bimetallic methanation catalyst and preparation and application thereof

    CN104209127A